Evaluating the effect of logbook as viewed by the juniors and seniors at Shiraz school of dentistry - Elham Mazareie; Shahla Momeni Danaei; Sahar Hosseininezhad; Mahsa Nili (Kerman University of Medical Sciences, 2016)
Background & Objective: Evaluation is a process that identifies and describes the effectiveness of all aspects of education The use of logbooks as an aid in education and assessment might provide the possibility for a more uniform training The aim of this study was to evaluate the effect of logbook on students perspective in each of the 10 departments of dental school Methods: In this crosssectional survey a questionnaire consisting of 16 standardized items each scored on a 5point Likert scale (0 to 4) was used From among the collected forms 50 completely filled questionnaires were entered into the study The validity of the questionnaire was approved by a group of 10 experts and its reliability was confirmed using Cronbachs α (094) Tukeys test and oneway ANOVA were used for data analysis Results: In all departments there was agreement between the students logbook scores and final grades In addition the ability to find learning weaknesses via logbooks had the lowest score whereas clear statement of learning objectives for each subject and requirement obtained the highest score Usefulness of written clinical procedures in logbooks had the highest score in the Departments of Endodontics Removable Prosthodontics Fixed Prosthodontics and Pediatrics Conclusion: The logbook is a practical and useful assessment tool for evaluating students and achieving learning objectives It clearly states the educational objectives and clarifies the minimum requirements for each department However there is a need for the mutual cooperation and commitment of both the students and educators which requires time and the better establishment of this method